Model of spiritual nursing care in enhancing quality of life of patients with heart failure - Okviasanti, Fanni; Yusuf, Ah; Kurniawati, Ninuk Dian; Harianto, Susilo; Abd Nasir; Supatmi (Journal of the Pakistan Medical Association, 2023)
Objective: To develop a spiritual nursing care model to improve the quality of life of heart failure patients. Method: The cross-sectional study was conducted at two government hospitals in East Java, Indonesia, from August to November 2019, and comprised patients of either gender aged 30 years or above having classic heart failure symptoms of weariness, ankle swelling and dyspnoea. Standardised questionnaires were used to collect data regarding disease, psychosocial, spiritual, demographic and environmental factors as well as stressors, formation of meaning, coping strategy, spiritual wellbeing, and quality of life. Data was analysed using partial least squares structural equation modelling. Results: Of the 222 patients, 124(55.9%) were males and 98(44.1%) were females. The overall mean age was 57.7±9.96 years. Overall, 33(14.9) patients were suffering from heart failure for >5 years, 36(16.2) had been hospitalised >5 times, and 8(3.6%) had no health insurance cover. Psychosocial (T=2.110), spiritual (T=1,998) and environmental (T=2,019) factors had an effect on the ability to assess stressors. Disease (T=5.497), spiritual (T=3.596) and environmental (T=3.172) factors had an effect on spiritual wellbeing. Disease (T=7.553), psychosocial (T=2.230) and environmental (T=2.625) factors affected the quality of life. The ability to assess stressors affected meaning formation (T=3.293), which had an effect on coping strategies (T=3.863), which, in turn, had an effect on spiritual wellbeing (T=9.776), and that affected the quality of life (T=2.669). Conclusion: The spiritual nursing care model was found to be influenced by disease, psychosocial and environmental factors as well as by spiritual wellbeing. Keywords: Adaptation, Psychological, Heart failure, Spirituality, Structural.